1992
DOI: 10.1021/jf00015a032
|View full text |Cite
|
Sign up to set email alerts
|

Persistent organochlorine residues in foodstuffs from India and their implications on human dietary exposure

Abstract: Foodstuffs collected from different regions in India were analyzed for the presence of HCH (BHC), DDT, HCB, aldrin, dieldrin, heptachlor, and PCBs. Significantly high levels of food contamination with HCH, DDT, aldrin, and dieldrin were evident throughout India. Dairy products and livestock meat are the prime sources of human dietary exposure to these chemicals. Concentrations of these organochlorine compounds in a few dairy products were above the maximum residue limits (MRLs) set forth by the FAO/WHO as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
3
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(64 citation statements)
references
References 28 publications
3
56
3
2
Order By: Relevance
“…The mean concentrations of o,p'-DDT was observed as 0.013 μg·g −1 in the buffalo's milk samples of the studied area which is less as reported by Ashnagar et al, 2009 [56]. Kannan et al (1992) evaluated milk from india and found levels of DDT as 0.110 mg/kg which was above those found in the present study [58].…”
Section: Pesticide Residuecontrasting
confidence: 74%
“…The mean concentrations of o,p'-DDT was observed as 0.013 μg·g −1 in the buffalo's milk samples of the studied area which is less as reported by Ashnagar et al, 2009 [56]. Kannan et al (1992) evaluated milk from india and found levels of DDT as 0.110 mg/kg which was above those found in the present study [58].…”
Section: Pesticide Residuecontrasting
confidence: 74%
“…All the four isomers of HCH were also detected in goat tissue under present study, but at levels lower than those detected earlier, as found in the earlier reports. Similarly, the levels of lindane reported in the present study (0.002 mg/kg-0.85 mg/kg) were below the level (0.004 mg/kg -1.611 mg/ kg) reported by Al-Omar et al (1985) in lamb from Baghdad and several other workers including Kannan et al (1992), who found lindane in the range of 0.005 mg/kg -1.1 mg/kg from different locations in India. Battu et al (1984) observed that pp l DDE constituted a major share (0.047 mg/kg) in goat tissue.…”
contrasting
confidence: 82%
“…Organo chlorine class of pesticides is now banned. Due to the excessive use of this class, leaves large concentration in vegetables [3].…”
Section: Introductionmentioning
confidence: 99%